2001
DOI: 10.1007/bf02234737
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal adenocarcinoma in patients under 45 years of age

Abstract: This study confirms the high frequency of predisposing conditions in young patients and that young age is not a poor prognostic factor for colorectal cancer. This underlines the importance of family screening, aggressive surveillance, and treatment in the young with known predisposing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 15 publications
3
19
2
Order By: Relevance
“…Of course, younger patients are likely to undergo more aggressive therapy including chemotherapy or repeated surgical resection for metastatic disease that may improve the poorer prognosis given for EOCRC. Although partly contradictory with older studies, some of which were global analyses based on registries, the present work provides reliable results for the same aforementioned reasons [32][35]. Overall, sporadic EOCRC presents as an aggressive disease with distal location, high tumor stage and no clear histological specificity.…”
Section: Discussioncontrasting
confidence: 82%
“…Of course, younger patients are likely to undergo more aggressive therapy including chemotherapy or repeated surgical resection for metastatic disease that may improve the poorer prognosis given for EOCRC. Although partly contradictory with older studies, some of which were global analyses based on registries, the present work provides reliable results for the same aforementioned reasons [32][35]. Overall, sporadic EOCRC presents as an aggressive disease with distal location, high tumor stage and no clear histological specificity.…”
Section: Discussioncontrasting
confidence: 82%
“…The exact cause of this difference is not known; however, it can be postulated that the higher proportion of younger patients in the underdeveloped countries can be a reason for this skewed finding [16]. However, more interesting is the hypothesis that sporadic early onset colorectal cancer is a biologically and clinically distinct entity, accounting for its aggressive presentation and poorer survival [16, 17, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that early onset colorectal cancer is a biologically and clinically distinct disease where younger individuals have more aggressive disease and worse survival [16, 17]. A recent population based study from Pakistan also showed that younger patients presented with disease which was more likely to be poorly differentiated and at a more advanced stage at diagnosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…These inconsistent could be explained by: First, the current definition of young CRC patients remains controversial. Although majority of studies in the literature used the cutoff age of 40 years to denote a young patients with CC [3], [4], [5], [6], [7], some other studies used the cutoff age of 30 years [4], [15], 25 years [16] or others [17], [18], [19]. Second, young age consisted wide age range of population, which maybe an inherent characteristic of heterogeneous, different composition of young subgroup may cause different results.…”
Section: Discussionmentioning
confidence: 99%